2006
DOI: 10.1016/j.joca.2005.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis cartilage histopathology: grading and staging

Abstract: The OARSI cartilage OA histopathology grading system appears consistent and simple to apply. Further studies are required to confirm the system's utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
1,689
1
33

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,891 publications
(1,789 citation statements)
references
References 45 publications
35
1,689
1
33
Order By: Relevance
“…5B), similar to the RBPjκ insufficiency. Quantification by grading systems (25) confirmed that the DAPT injection significantly suppressed OA development (Fig. 5C).…”
Section: Notch Signaling Enhances the Terminal Stage Of Endochondralmentioning
confidence: 58%
See 2 more Smart Citations
“…5B), similar to the RBPjκ insufficiency. Quantification by grading systems (25) confirmed that the DAPT injection significantly suppressed OA development (Fig. 5C).…”
Section: Notch Signaling Enhances the Terminal Stage Of Endochondralmentioning
confidence: 58%
“…This suppression was associated with the decreases in expressions of Mmp13, Vegfa, and Hes1, but not Col10a1, indicating prevention of the terminal stage of endochondral ossification by the RBPjκ insufficiency, similar to the Sox9-Cre;Rbpj fl/fl limb cartilage. Quantification by grading systems (25) confirmed that the RBPjκ insufficiency caused significant resistance to OA development (Fig. S1E).…”
Section: Notch Signaling Molecules Are Expressed and Activated Duringmentioning
confidence: 62%
See 1 more Smart Citation
“…The OARSI cartilage OA pathology assessment system provides six grades of OA involvement (46). In grade 1, the cartilage matrix undergoes swelling, abrasion and changes in the structure of the cartilage such as patchy condensation of collagen and gain or loss of chondrocytes.…”
Section: Features Of Articular Cartilage During Osteoarthritismentioning
confidence: 99%
“…Histological sections were numbered to obscure treatments and examined by two independent reviewers and scored using the OARSI scoring system. 33 The OARSI scoring system produced a score between 0 and 24 that was the mathematical product of the lesion grade and stage. Grade (0-6) indicated depth of the lesion where lesion stage corresponds to the area of abnormal cartilage as determined by India ink staining and histological examination of multiple (12)(13)(14)(15) sections of the femoral condyle.…”
mentioning
confidence: 99%